2018
DOI: 10.22271/ortho.2018.v4.i4e.50
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surgical treatment of inter-condylar humerus fracture with olecranon osteotomy approach

Abstract: Background: Inter-condylar fracture distal humerus in adults often pose a challenge to orthopaedic surgeons because of the complex anatomy, fracture pattern and limited bone stock of this region. Adequate exposure of the articular surface of the distal humerus and elbow joint is essential for operative stabilisation of complex distal humerus fracture. Various operative approaches have been recommended to access this difficult region which includes triceps splitting, triceps reflecting and trans-olecranon appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Transolecranon osteotomy provides excellent exposure of the joint surface; however, osteotomy-related complications are high. 9,12,17,31 Gainor et al reported a 30% osteotomy nonunion rate in ten patients treated for distal humerus fractures with a transolecranon osteotomy, followed up at 24 months. 54 Comparative level 1 or 2 studies have not shown superior outcome with any of the approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transolecranon osteotomy provides excellent exposure of the joint surface; however, osteotomy-related complications are high. 9,12,17,31 Gainor et al reported a 30% osteotomy nonunion rate in ten patients treated for distal humerus fractures with a transolecranon osteotomy, followed up at 24 months. 54 Comparative level 1 or 2 studies have not shown superior outcome with any of the approaches.…”
Section: Discussionmentioning
confidence: 99%
“…10 The olecranon osteotomy is the workhorse surgical approach to treat AO type C fractures as it provides excellent surgical exposure of the articular surface and unrestricted plating options. [10][11][12] There have been several documented concerns about the osteotomy, which include, from Goda et al, delayed union and non-union (10%), malunion and prominent hardware (25%); from Gofton et al, non-union (13%), heterotopic ossification (30%), infection (9%), reoperation rate (34%); from Kundel et al, non-union (12%), infection (8%), failure of fixation (4%), heterotopic ossification (49%); from Meldrum et al, non-union (3%), infection (3%), implant irritation (22%). [13][14][15][16] Somerson et al, in a recent paper, reported the olecranon osteotomy to be the only independent predictor for reoperation after fixation of intra-articular distal humerus fractures.…”
Section: Introductionmentioning
confidence: 99%